Konsep Pemikiran Imam Al Ghazali dalam Relevansi Pola Pendidikan Islam Indonesia dalam Era Globalisasi - Mariyo Mariyo (Journal on Education, 2023)
This study aims to find out about Islamic education in the global era based on the educational concept of Imam Al Ghazali. This type of research is descriptive qualitative research. In the field of education, Imam Al Ghazali applies a code of ethics for educators and students, educational and learning methods which have their respective emphases and stages. The result of this study is the concept of educational thought of Imam Al Ghazali and its relevance in Indonesian Islamic education emphasizing cognitive, psychomotor, and motor aspects. The cognitive aspect is carried out by emphasizing mastery of subject matter by memorizing at the basic level and understanding at a more advanced level. The psychomotor aspect emphasizes the practice of subject matter through amaliyah worship. While the affective aspect is carried out by appreciating the lessons in everyday life.